2013
DOI: 10.2147/opth.s38915
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional results of indirect diode laser treatment for retinopathy of prematurity from 1999 to 2003 in Kuwait

Abstract: PurposeThe purpose was to report the structural, visual, and refractive outcomes of infants treated for retinopathy of prematurity (ROP) with laser and to identify the risk factors for unfavorable outcomes.Materials and methodsThe charts of infants with severe ROP treated by diode laser in a tertiary center during the period April 1999 to November 2003 were reviewed. Treated infants were followed up for fundus examination, visual acuity assessment, and cycloplegic refraction. Data regarding ocular risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Severe ROP is likely to affect ocular structures more so than subcortical or cortical structures; however, if ROP affects the initial processing of visual information, which in turn affects the development of the eye, then these changes may ultimately affect the way subcortical and cortical pathways develop such as ocular dominance columns or other visual pathway networks. Unsurprisingly, visual acuity remained significant after controlling for important confounders, given the reported relationship between ROP and refractive errors in this population (Kushner, ; Nissenkorn et al ., ; Quinn et al ., ; Snir et al ., ; Wani et al ., ; Yang et al ., ). Several studies have discussed the possible relationship between preterm birth, ROP, ocular growth, and development, with several mechanisms proposed as contributing factors (Fielder & Moseley, ; Fielder et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe ROP is likely to affect ocular structures more so than subcortical or cortical structures; however, if ROP affects the initial processing of visual information, which in turn affects the development of the eye, then these changes may ultimately affect the way subcortical and cortical pathways develop such as ocular dominance columns or other visual pathway networks. Unsurprisingly, visual acuity remained significant after controlling for important confounders, given the reported relationship between ROP and refractive errors in this population (Kushner, ; Nissenkorn et al ., ; Quinn et al ., ; Snir et al ., ; Wani et al ., ; Yang et al ., ). Several studies have discussed the possible relationship between preterm birth, ROP, ocular growth, and development, with several mechanisms proposed as contributing factors (Fielder & Moseley, ; Fielder et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in care, long‐term follow‐up of children with regressed ROP has shown that there is an increased incidence of strabismus, amblyopia and refractive errors, in particular myopia, compared with preterm infants without ROP and with full‐term infants (Kushner, ; Nissenkorn, Yassur, Mashkowski, Sherf, & Ben‐Sira, ; Quinn et al ., ; Snir, Nissenkorn, Sherf, Cohen, & Ben Sira, ; Wani et al ., ; Yang, Wang, Shih, & Hsu, ). For example, Nissenkorn et al .…”
Section: Introductionmentioning
confidence: 99%
“…Low BW and small GA are known to be risk factors for the development of ROP (18) . Many previous studies included treatment groups mainly consisting of preterm patients weighing <1000 g and aged <28 weeks (10,(19)(20)(21) . In our study, consistent with previous reports, the average BW and GA in patients who received treatment were 900 g and 27 weeks, respectively; although these values were higher among referred patients, they were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Zone 1 ROP, which is less sensitive to laser/cryotherapy and demonstrates poorer anatomic and visual outcomes (Good and Early Treatment for Retinopathy of Prematurity Cooperative, 2004), (Wani et al, 2013, Gunn et al, 2014, Gole et al, 2011, is correlated with vessel development by both vasculogenesis and angiogenesis, but vasculogenesis is only responsible for the formation of the primordial vessels in a small region surrounding the optic nerve head (Hughes et al, 2000) . Even within the central one third of the retina surrounding the optic disc, angiogenesis contributes to increasing vascular density once the primordial vessels are formed.…”
Section: Unique Susceptibility Of Posterior Rop: Basis In Vasculogenimentioning
confidence: 99%
“…The worst visual outcomes occur in those infants with aggressive posterior ROP (AP-ROP) which typically occurs in Zone I. The visual outcomes for laser treatment of AP-ROP are generally poor (Wani et al, 2013, Gunn et al, 2014 despite good anatomical success rates (Sanghi et al, 2014). Early vitreous surgery has been advocated but the results remain poor especially if fibrovascular growth has already reached the vitreous base when surgery is performed (Azuma et al, 2013).…”
Section: Outcomes After Laser For Ap-ropmentioning
confidence: 99%